2022
DOI: 10.1182/blood.2022016175
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-induced T-cell responses against SARS-CoV-2 and its Omicron variant in patients with B cell–depleted lymphoma after CART therapy

Abstract: Patients receiving CD19 CAR T-cell therapy for relapsed/refractory lymphoma experience prolonged and profound B-cell aplasia and hypogammaglobulinemia, placing them at a higher risk for severe COVID-19. Independently, Oh et al and Atanackovic et al demonstrate that despite attenuated humoral response to mRNA-based vaccines, patients demonstrate normal or heightened functional T-cell responses, including antiviral T-cell activity against SARS-CoV-2 variants including Omicron. Collectively, these data reinforce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…Nevertheless, detectable SARS-CoV-2-specific CD8+ T cells in the seronegative patients were largely not polyfunctional with CD8+ T cells that produce predominantly only IFN-γ [ 94 ]. Extending these results, a recent study by Atanackovic et al revealed the development of virus-specific CD4+ and CD8+ T cells in B cell lymphomas after treatment with chimeric antigen receptor T (CAR-T) cells and a third SARS-CoV-2 mRNA vaccine dose, while antibody responses are lacking [ 95 ]. Similarly, patients undergoing anti-CD20 treatment generate vaccine-induced T cells, even if antibodies are undetectable [ 78 , 96 ].…”
Section: Sars-cov-2-specific T Cells In Cancer Patientsmentioning
confidence: 99%
“…Nevertheless, detectable SARS-CoV-2-specific CD8+ T cells in the seronegative patients were largely not polyfunctional with CD8+ T cells that produce predominantly only IFN-γ [ 94 ]. Extending these results, a recent study by Atanackovic et al revealed the development of virus-specific CD4+ and CD8+ T cells in B cell lymphomas after treatment with chimeric antigen receptor T (CAR-T) cells and a third SARS-CoV-2 mRNA vaccine dose, while antibody responses are lacking [ 95 ]. Similarly, patients undergoing anti-CD20 treatment generate vaccine-induced T cells, even if antibodies are undetectable [ 78 , 96 ].…”
Section: Sars-cov-2-specific T Cells In Cancer Patientsmentioning
confidence: 99%
“…The incidence of COVID‐19 was similar between responders and impaired responders, suggesting the contribution of cellular immunity to its prevention. A previous report evidenced vaccine‐induced SARS‐CoV‐2‐specific T‐cell response among lymphoma patients treated with CAR‐T therapy, leading to salvage the profound inhibition of humoral immune system 26 …”
Section: Discussionmentioning
confidence: 98%
“…A previous report evidenced vaccine-induced SARS-CoV-2-specific T-cell response among lymphoma patients treated with CAR-T therapy, leading to salvage the profound inhibition of humoral immune system. 26 Among 552 patients receiving the first dose of vaccine, 5 (0.9%) patients did not receive a second dose due to vaccine-related events, including GVHD aggravation (n = 4) and AE (n = 1). Additional cases of GVHD flare occurred in 0.2% and 0.4% of patients after the first and the second dose, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent research have unraveled the protective effect of an early T cell response, especially early CD4+ T cells [9] , [10] , as well as the devastating effects of a completely depleted T cell response, even with a proper humoral response [8] . Available vaccines have been shown to induce rapid and coordinated CD4 + and CD8 + T cell responses, including against recent variant of concerns [9] , [11] and in B-depleted patients with cancer [12] , [13] , [14] .…”
Section: To the Editormentioning
confidence: 99%